Die Filistynse plaag in 1 Samuel 5-6: medies-teologiese verlarings (Acta Theologica)
According to the Old Testament (1 Samuel 5 and 6) the Ark of the Covenant was on occasion captured from the Israelites by the Philistines and taken to their own country. Subsequently, a plague, attributed to the Ark, erupted among the Philistines, and led to the Ark being returned to Israel after seven months. The plague consisted of abscesses or tumours, without indicating a specific anatomical location. There have in time been various suggestions of what the plague represented. Bubonic plague has often been mentioned as a possible cause, but the symptoms do not correspond with those mentioned in the Septuagint or the Vulgate, and the first recorded case of bubonic plague was in the 6th century AD. We thus consider that the 1st century AD Jewish-Roman historian, Josephus, was correct when he stated that the Philistine epidemic was dysentery: bacillary dysentery is a disease caused by a micro-organism which spreads from person to person by way of oral-faecal infection in a situation where there is poor hygiene, as was probably the case in 11th century BC Philistia.